Oral health and oral quality of life in inactive patients with familial Mediterranean fever without amyloidosis - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2013)
Objectives. The aim of this study was to investigate oral and general health-related quality of life (QoL) in patients with familial Mediterranean fever (FMF) disease. Methods. In this cross-sectional study, 45 patients with FMF, 50 age- and sex-matched healthy controls (HC), and 50 patients with Behcet's disease (BD) as the disease control group were included. FMF disease activity was evaluated by using the FMF-severity score, as well as with erythrocyte sedimentation rate (ESR), and serum C-reactive protein and fibrinogen levels. Oral health-related QoL and general QoL were evaluated using oral health impact profile-14 (OHIP-14) and Medical Outcomes Short-Form Health Survey Questionnaire 36 (SF-36), respectively. Results. Only the numbers of extracted teeth (4.13 +/- 4.72 vs. 1.55 +/- 3.6) and filled teeth (2.33 +/- 3.19 vs. 0.66 +/- 1.46) were significantly higher in FMF group compared to HC group (p=0.005 and p=0.013, respectively). OHIP-14 score was significantly higher in FMF and BD groups compared to HC group. In FMF patients, OHIP-14 score was positively correlated with the number of extracted teeth (r=0.38, p=0.010), while the number of carious teeth was positively correlated with ESR (r=0.43, p=0.003). When FMF patients were sub-classified according to disease severity, no significant difference was observed with respect to oral health status. Conclusion. In patients with FMF, some of the parameters of oral health status were found to be worse compared to HC group. Tooth loss appears to be to be a critical factor contributing to impaired oral QoL. In general, oral health status in FMF patients is better than in BD patients.
Keywords: FMF; oral health; quality of life; BEHCETS-DISEASE; TOOTH LOSS; SEVERITY; FMF; INFLAMMATION; EXPRESSION; DIAGNOSIS; ARTHRITIS; CHILDREN; CRITERIA